Phage-induced changes in Vibrio cholerae: serotype and biotype conversions. - Ogg, J E (1978)
Phage infection of Vibrio cholerae resulted in antigenic changes. A strain of biotype cholerae serotype Ogawa was converted into serotype Hikojima and gained the ability to synthesize antigenic factor C. Some phage-converted strains remained stable after subculture and were immune to superinfection with the same phage. The stable converted strains were lysogenic and released phage having a host range similar to the phage of the donor strain. Reinfection of unstable converted strains which had "lost" antigen C yielded types able to again synthesize this antigen. The polymyxin resistance character was expressed in the biotype cholerae strain after infection with some phage preparations. These polymyxin-resistant strains possessed three main characteristics of El Tor vibrios. The phage-induced changes described provide V. cholerae with the potential for innumerable genetic combinations.